Analyzing the Roles of Country Image, Nation Branding, and Public Diplomacy through the Evolution of the Modern Olympic Movement - Dubinsky Yoav (Sciendo, 2019)
Since the Ancient Greek athletics and through the revivals of the Olympic Movement and the first modern Olympics in Athens in 1896, countries, cities and governments have sought to take advantage by hosting Olympic Games and other sport events. The purpose of this study is to analyze the different facets of country image through the evolution of the Olympic movement. Countries and governments used and will continue to use the Games to renovate infrastructure, build new facilities, expose local products and new technologies, leverage tourism, improve the local and international political and social image, promote tourism and show superiority on the sports field that will enable them to try and reach their economic, political and social goals. The article is significant as it analyzes how countries, cities, communities, and other pressure groups used the Olympic Games, since the revival of the Olympic Movement in the late 19th century, the new traditions after World War I, the political era after World War II and during the Cold War, the commercialized era and the legacy-oriented era in early 21st century.